Identification of induced polarization of submarine hydrocarbons in marine controllable source electromagnetic exploration - Qiu, Ning; Luo, Zhixin; Fu, Qicheng; Sun, Zhen; Chang, Yanjun; Du, Bingrui (Frontiers in Earth Science, 2023)
The identification of hydrocarbons buried on the seafloor is highly dependent on geophysical exploration capabilities. Seismic exploration has been an important tool in providing information on submarine stratigraphy before offshore drilling, but it is challenge to identify the nature and saturation of the fluid in the structure by seismic exploration. Of all the physical properties, electrical parameters are the most sensitive to the fluids in the reservoir and would be able to be combined with seismic data to improve the identification of hydrocarbons at depth. However, the marine controlled-source electromagnetic method usually only considers the effect of electromagnetic induction and ignores the induced polarization (IP) effects. The IP effects can occur in the stratum where the reservoir is located due to a variety of factors, so taking into consideration of the IP effects will make the modeling more reasonable, and thus give more accurate results when interpreting and processing the data. We have used the integral equation method for modeling, adopted the scattering and superposition method to calculate the dyadic Green's function required in the study, replaced the real resistivity with a complex resistivity that takes into account the IP effects, investigated the response patterns of different ion polarization models, analyzed the influence patterns of various model parameters. These investigations will provide important contributions to the study of submarine hydrocarbon detection. The field data also show the amplitude and phase response results of polarizability show that gradually increases from the offset.